Evaluating the successful and sustainable implementation of evidence-based innovations in health systems in low- and middle-income countries: a maturity model approach - Leonard, Elizabeth (Stellenbosch : Stellenbosch University, 2023)
Thesis (PhD)--Stellenbosch University, 2023.